2005
DOI: 10.1007/s10995-005-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Race and Ethnic Disparities in Cervical Cancer Screening in a Safety-Net System

Abstract: Culturally competent, community-based care for women is needed to increase Pap smear screening among minority groups, especially Hispanic immigrant and Hispanic American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
5
24
0
1
Order By: Relevance
“…42 Cervical cancer screening rates for women from minority groups are consistently below the rates of nonminority women. [43][44][45] Using data for self-reported Pap screening behavior from the Behavioral Risk Factor Surveillance System (BRFSS), Coughlin et al 46 found that women from minority racial=ethnic groups, lower education level, and lower income or the unemployed were less likely to participate in screening.…”
Section: Discussionmentioning
confidence: 99%
“…42 Cervical cancer screening rates for women from minority groups are consistently below the rates of nonminority women. [43][44][45] Using data for self-reported Pap screening behavior from the Behavioral Risk Factor Surveillance System (BRFSS), Coughlin et al 46 found that women from minority racial=ethnic groups, lower education level, and lower income or the unemployed were less likely to participate in screening.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies focusing on minority racial/ethnic populations indicate that lack of health insurance, lower level of education, lack of continuity of care, and lower use of public services were associated with lack of adherence to annual Pap smears. [25][26][27] Unfortunately, we did not have data to assess income, employment, or education. All of our patients were either insured or were eligible to receive primary and gynecological care paid by the Ryan White CARE Act support, which does not require an enrollment wait time or other special procedure in our region, so insurance was not likely a barrier in this study.…”
Section: Discussionmentioning
confidence: 99%
“…43 Two studies focused on Pap smears for immigrant patients using telephone surveys concluded that awareness of a safety net systems and culturally competent-based care also is needed to improve quality of care among minority groups. 44,45 CONCLUSION This is one of the first studies to have attempted to address the role of a system of care on reducing ethnic disparities in health care. The IOM report on "Unequal Treatment" underscored the need for such studies.…”
Section: Discussionmentioning
confidence: 99%